2017
DOI: 10.1002/stc.1986
|View full text |Cite
|
Sign up to set email alerts
|

Inertial mass damper for mitigating cable vibration

Abstract: Summary Stay cables used in cable‐stayed bridges are prone to vibration due to their low‐inherent damping characteristics. Many methods have been implemented in practice to mitigate such vibration. Recently, negative stiffness dampers have gained attention because of their promising energy dissipation ability. The viscous inertial mass damper (VIMD) has been shown to have properties similar to negative stiffness dampers. This paper examines the potential of the VIMD to enhance the damping, and mitigate the vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 52 publications
1
53
0
Order By: Relevance
“…The Equation in analytical form gives all possible solutions of taut cable with a viscous damper and a concentrated mass. Further comparison showed the results of this analytical solutions were the same as the results by numerical method as stated by Lu et al as also stated in the following section.…”
Section: General Problem Formulationssupporting
confidence: 82%
See 2 more Smart Citations
“…The Equation in analytical form gives all possible solutions of taut cable with a viscous damper and a concentrated mass. Further comparison showed the results of this analytical solutions were the same as the results by numerical method as stated by Lu et al as also stated in the following section.…”
Section: General Problem Formulationssupporting
confidence: 82%
“…Figure shows that if ϕ is not zero, η in Equation will firstly decrease and then reach to a minimum value as α decrease and then increases to an infinite value as α tends to minus infinity. Figure also shows the comparison between solutions of Equation to results of Galerkin's method with 499 trigonometric functions together with one static deflection at damper location shape as shape functions . The number of shape functions is increased to be 500 to reduce the error of Galerkin's method for the mode shape of cable is hyperbolic rather than trigonometric when β = 0 (Equation ).…”
Section: Special Limit Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the research results above, it has been confirmed that the negative stiffness is capable of improving the energy dissipation ability of a conventional damper. In view of such benefits, several passive negative stiffness dampers were also proposed to enhance the vibration control performance of the cable, such as a viscous damper with a negative magnetic stiffness spring [44], an oil damper with two pre-compressed springs [45], and a viscous inertial mass damper [46].…”
Section: Effect Of Negative Stiffness Of the Damper On The Performancmentioning
confidence: 99%
“…In order to improve the performance of the TMD, the tuned mass damper inerter (TMDI), which combines the inerter with the TMD, was proposed to reduce the large mass in conventional TMD by the mass amplification effect of the inerter . When the mass in TMDI is entirely replaced by the inerter, the TMDI system becomes the tuned inerter damper system, which has been studied in many aspects . Recently, an alternative that combining the conventional BIS with the TMDI proposed by De Domenico and Ricciardi has been proved to be a more effective vibration control strategy with the comparison of BIS coupled with TMD as well as the comparison of BIS with supplementary damping.…”
Section: Introductionmentioning
confidence: 99%